2011
DOI: 10.1111/j.1741-3729.2011.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Characteristics, Custody Arrangements, and Adolescent Psychological Well‐being After Lesbian Mothers Break Up

Abstract: As part of the largest, longest running prospective American study of same‐sex parent families, the present investigation examined relationship dissolution in planned lesbian families. Data were collected from 40 separated couples and their 17‐year‐old adolescent offspring—19 girls and 21 boys. Nearly all breakups occurred before the former couples could have obtained the legal equivalent of same‐sex marriage in their state of residence. A majority of the mothers rated the communication with their ex‐partners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 35 publications
5
39
0
10
Order By: Relevance
“…For example, Gartrell, Bos, Peyser, Deck, and Rodas (2011) found that the rate of partnership dissolution in the National Longitudinal Lesbian Family Study was higher than the divorce rate among age-matched heterosexual parents in the U.S. National Survey of Family Growth. However, separation rates are likely to be higher than divorce rates, and it is worth bearing in mind that few of the lesbian couples had access to same-sex marriage or civil union status.…”
Section: Parentingmentioning
confidence: 99%
“…For example, Gartrell, Bos, Peyser, Deck, and Rodas (2011) found that the rate of partnership dissolution in the National Longitudinal Lesbian Family Study was higher than the divorce rate among age-matched heterosexual parents in the U.S. National Survey of Family Growth. However, separation rates are likely to be higher than divorce rates, and it is worth bearing in mind that few of the lesbian couples had access to same-sex marriage or civil union status.…”
Section: Parentingmentioning
confidence: 99%
“…We know that legal inequality, namely the inability for both parents when coupled to be legally recognized as parents, has negative consequences in terms of the non-legal parent having less power; but does that translate into the relationship quality among (nonlegally recognized) parents and their children? A study by Gartrell et al (2011) suggests yes insofar as children reported higher levels of closeness with both parents in families who had done a second-parent adoption. Future research should continue to explore whether and how the law can affect parent-child relationship quality.…”
Section: Discussionmentioning
confidence: 99%
“…Respondendo a estes questionamentos, os estudos concluem que a sexualidade dos pais e das mães não é fator determinante no bem-estar e ajustamento psicológico dos seus filhos (Bos, 2010;Erich, Kanenberg, Case, Allen, & Bogdanos, 2009;Gartrell & Bos, 2010;Oliva, Arranz, Parra, & Olabarrieta, 2014;Perlesz & McNair, 2004;Wainright, Russell, & Patterson, 2004). Nestes casais, há flexibilidade no desempenho de funções parentais (Perlesz & McNair, 2004;Rodriguez & Paiva, 2009), a relação parental tende a ser próxima, privilegiando o respeito e a aceitação das diferenças (Gartrell, Bos, Peyser, Deck & Rodas, 2011;Goldberg & Allen, 2013 …”
Section: Figura 1 Fluxograma Da Seleção Dos Artigosunclassified
“…Nestes casais, há flexibilidade no desempenho de funções parentais (Perlesz & McNair, 2004;Rodriguez & Paiva, 2009), a relação parental tende a ser próxima, privilegiando o respeito e a aceitação das diferenças (Gartrell, Bos, Peyser, Deck & Rodas, 2011;Goldberg & Allen, 2013 …”
Section: Figura 1 Fluxograma Da Seleção Dos Artigosunclassified
See 1 more Smart Citation